The Influence of Viral Marketing and Brand Image on Purchase Decisions through E-Trust: Study on Avoskin Skincare Customers - Chairatun Nisa’il Firdausi Madjid; Sudarmiatin; Agus Hermawan (CV ODIS, 2022)
Viral marketing is a trend that can attract consumers' attention through social media. This study aims to determine the effects of viral marketing and brand image on purchasing decisions through e-custrust. This research is a quantitative study using the SPSS 22 program. The population of this study is Avoskin Instagram followers. The sample in this study was 200 respondents. In addition, to test the eligibility of the instrument, test validity and reliability used conventional hypothesis tests and hypothesis tests—path analysis technique. The results of this study indicate that (1) viral marketing has a positive and significant effect on electronic tractrum, (2) brand image has a positive and significant effect on marketing e-traust viruses (3) has a positive and significant effect on purchasing decisions, (4) The positive and significant influence of the brand image on purchasing decisions, (5) e-custrust has a positive and significant effect on purchasing decisions. Based on the study results, the advice for company players is to provide more attractive advertisements for consumers, create a more attractive product conception and determine products according to their needs